Analisis faktor-faktor yang mempengaruhi tingkat cerai gugat di Kota Pekanbaru - Novie Oktary; Lapeti Sari; Yusni Maulida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aims to analyze the factors that affect the level of contested divorce in Pekanbaru City which comprised the factors of education,income, employment status and age of first marriage. The population of this research are women who divorce (contested divorce)in 2012. Samples in this research using simple random sampling to obtain 89 respondents. This research analyzed using deskriptive qualitative method by using observation and questionnaires were given to each respondent. From the questionnaires result and the analysis that have been done, indicating that education and income factors significantly influence the contested divorce. While employment status factor and the age of first marriage factor does not affect the contested divorce.Keywords: divorce, contested divorce, pekanbaru